Revisión de métodos para el tratamiento de aguas residuales de la industria cosmética (2023)
The disposal of wastewater is considered one of the most frequent pollution problems for the environment from the cosmetic sector due to the large amount of contaminants present in it, for this reason, it is important to highlight that there must be good water treatment. residuals, which can have different routes and will depend on the conditions of each company. To achieve this, this project proposes the comparison of different methodologies for the treatment of wastewater from the cosmetics industry, which allows compliance with current regulations and reducing the amount of certain contaminants. These methodologies will serve as a guide and can be adapted to the different conditions or situations that companies present, in order to improve their water treatment process or generate added value by changing some stage of their treatment process.